State-Contingent Government Debt: a New Database - Gonçalo Pina (Credit and Capital Markets – Kredit und Kapital, 2022)
State-contingent government debt has been proposed as a way to reduce costly debt crisis. However, markets for this type of debt remain very limited, for reasons that are not yet fully understood. This paper describes a new database covering state-contingent government debt issued between 1863 and 2020. Based on these data, this paper shows stylized facts regarding the main design features, and market performance, of state-contingent government debt. It also provides a brief history of state-contingent government borrowing, which is contextualized with a simple theoretical model of state-contingent debt. The results show that there have been several small, heterogeneous, issuances of state-contingent debt, which resemble pilot runs in this new asset class. The paper concludes with some common challenges associated to state-contingent government debt.
Keywords: G1; N2; H63; 330; State-Contingent Debt; GDP-Linked Bonds; Public Debt